Designing Inclusive Learning Environments in Vocational Education through the EKEE Learning Model - Karoso, Subianto; Pujosusanto, Ari; Rinaldi, Cherry; Enie Wahyuning Handayani (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
This study examines the role of the EKEE (Exploration, Creation, Expression, and Evaluation) learning model in designing inclusive learning environments in Indonesian vocational secondary schools. The research is grounded in the need for pedagogical approaches that not only support the development of vocational competencies but also ensure equitable participation, meaningful learning experiences, and holistic human development for students with diverse abilities and learning needs. A qualitative approach with an implementative design was employed in inclusive vocational school classrooms. Data were collected through classroom observations, in-depth interviews with teachers and students, and analyses of learning documentation. The data were subsequently analysed using thematic analysis. The findings indicate that the EKEE learning model effectively supports inclusive learning by embedding flexibility, collaboration, and reflection throughout all stages of the learning process. The exploration stage provides safe and accessible entry points for learning, while the creation stage facilitates differentiated and collaborative learning activities. The expression stage enables diverse and authentic demonstrations of learning outcomes, and the evaluation stage promotes reflective, fair, and process-oriented assessment practices. These integrated stages contribute to increased student engagement, confidence, social interaction, and meaningful participation in learning. The discussion highlights that inclusivity within the EKEE model is operationalized through intentional learning design rather than merely through structural placement. This approach aligns with constructivist, sociocultural, and humanistic learning perspectives. The study concludes that the EKEE learning model offers a flexible and humanistic pedagogical framework for inclusive vocational education, supporting both vocational competency development and holistic learner growth. The model also demonstrates potential for adaptation across various vocational fields to promote equitable and sustainable inclusive learning practices.